PENINGKATAN KUALITAS PRODUK PAD LINE PADA MESIN GLUE NOTE BOOK P 15-42/13 DENGAN METODE TAGUCHI A TTRIBUTE (STUDI KASUS DI PABRIK KERTAS MOJOKERTO) - Evii Rachma Wijayanti; Haryono Haryono (Jurnal Teknobisnis, 2005)
One of the products of PT X, a paper manufacturing industry, is Pad Line Book. In order to maximize profit, PT X tried to reduce the production cost by maximizing defect. The current defect is approximately 5,560%. This research used Six Sigma quality method for improving the quality. The method consisted of five steps: i.e.Define- Measure-Analyze-Improve-Control. Define step was used to identifi defect root cause, using tool such as percentage control chart, while measure step is used to identify the type of defects. Analyse step defined the process variables including the levels that affect the quality significantly using Taguchi method matrix experiment (Orthogonal Array). The improve step defines the optimal response developed by Taguchi called Signal to Noise Ratio. The last step, control step provides the company with information on process variables that gives maximum contribution to achieve optimal response solution. By using attribute Taguchi method based on Six Sigma step, the process variables including levels combination that contributes to optimal solution all identified. For producing the Pad Line Books the combination was as follows; speed 400 m/s, glue pump pressure 3 bars, roll distance 0,3 m and temperature 550 Celcius. The overall quality improvement was 67,28% and the improvement itself grew from 4,23 six sigma to 4,33 six sigma.